P328 An overexpression screen identifies Csa25 as a novel cellular morphogenesis regulator in the human fungal pathogen Candida albicans. (20th September 2022) - Brahma, Priya; Jaitly, Priya; Das, Abhijit; Goyal, Rohit; Legrand, Melanie; d'Enfert, Christophe; Sanyal, Kaustuv
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Objective: Morphological plasticity is one of the key attributes of microbial pathogens contributing to the successful establishment of infection in host tissues. Candida albicans, an opportunistic human fungal pathogen, lives as a commensal in the gut, skin, and genitourinary tracts of most healthy individuals. The budding yeast form helps it to disseminate easily in the host system, and the filamentous form (hypha and pseudohypha) is believed to invade the host tissue. Strikingly, alterations of gene expression that block cell cycle progression at different stages additionally lead to aberrant cellular morphology in C. albicans . While various morphological states of C. albicans have been well-studied, the search for key players bringing about these changes is far from complete. This is supported by the fact that ∼70% of the C. albicans proteome remains functionally uncharacterized. Thus, the primary objective of our study was to identify novel regulators contributing to cellular morphogenesis in C. albicans . Method: In our current study, we screened an overexpression library of C. albicans ORFeome generated to identify novel regulators contributing to chromosome stability (CSA) in C. albicans . The screen involved overexpression of each gene using a tetracycline-inducible promoter for a duration of 12 h, followed by microscopy-based observations to identify associated aberrant cellular morphologies. Results: Screening of overexpression library of the C. albicans ORFeome identified 14 unique Candidate genes from 1389 genes screened. While the functions of half of them have been verified in C. albicans, the remaining seven genes are not functionally characterized. Each of the seven uncharacterized genes was predicted to be non-essential for viability in C. albicans . Bioinformatic analysis predicts one of these proteins, Csa25, to be carrying a point centromere-specific kinetochore protein Ndc10-like DNA-binding domain at its N-terminus spanning over a region of 273 amino acids. Sub-cellular localization indicates this protein to be present throughout the nucleus at all stages of the cell cycle. Strikingly, overexpression of this protein led to yeast cells forming chains connected by septa, as visualized by calcofluor staining, without hampering nuclear segregation. In addition, a large proportion of cells overexpressing Csa25 were unable to exhibit hyphal morphology when subjected to hyphae-inducing conditions. Conclusion: In conclusion, our study identified Csa25 as a novel morphogenesis regulator involved in the negative regulation of yeast-hyphae transition in C. albicans . Further studies based on host-pathogen interaction will identify the critical role of Csa25 in the pathobiology of C. albicans and its survival in host-specific niches.